Chitosan/polypyrrole hybrid film as multistep electrochemical sensor: sensing electrical, thermal and chemical working ambient. (August 2022) - Shabeeba, Aranhikundan; Ismail, Yahya A.
Highlights: An electroactive Cs/PPy hybrid film was fabricated via chemical coating of PPy on Cs film. The hybrid film exhibited an electrical conductivity of 1.4 Scm -1 . The biomimetic redox reactions of Cs/PPy hybrid film sense the working electrical, chemical and thermal energetic conditions. The voltammetric redox charge senses the electrolyte concentration. Any electrochemical devices based on Cs/PPy hybrid film will be multifunctional (dual sensing-actuators). Abstract: The reactive sensing capabilities of a mechanically stable chitosan/polypyrrole hybrid film fabricated through an in situ chemical polymerization of pyrrole are presented. The sensing abilities studied as a function of applied current, working temperature and electrolyte concentration revealed that the film can act as a multi-step electrochemical macromolecular motor, replicating basic elements of biological functions. The electrical energy consumed is a linear function of working electrical and thermal condition and a logarithmic function of electrolyte concentration. The extension of reaction (coulovoltammetric charges) is a function of and senses the working chemical ambient. The conformational changes of polymer chains (multi-step sensing motors) during reaction through the cooperative actuation make the coulovoltammetric charge a self-sensor of the working energetic conditions. This similarity of cooperative actuation of polymeric chains in biological muscles in simultaneously sensing the working condition suggests the possibility of constructing biomimetic simultaneous sensing motors using flexible chitosan/polypyrrole film with only two connecting wires. Graphical abstract: Image, graphical abstract